Peranan Guru dalam Penanaman Karakter Disiplin dan Tanggung Jawab Siswa melalui Pembelajaran IPS : Studi Kasus Siswa Kelas VII SMPN 1 Ngunut - Eprinda Nurro'in Habibah; Binti Maunah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study focuses on the development of student character, particularly in terms of discipline and responsibility, at SMPN 1 Ngunut, an outstanding school in Tulungagung Regency. Seventh-grade students are in a transitional phase from elementary to junior high school, making them vulnerable to the influences of their environment and the changing times. Based on observations, many students have not yet demonstrated disciplined behavior, such as arriving on time, completing tasks, cheating during exams, and not paying attention to teachers while learning. This study aims to identify effective Social Studies (IPS) teaching strategies for shaping students' character. The research focuses on (1) the role of teachers as demonstrators in developing disciplined and responsible character through IPS learning, (2) effective strategies employed by teachers to cultivate discipline and responsibility in students, and (3) potential solutions to improve the quality of IPS learning in instilling discipline and responsibility. The method used is descriptive qualitative research with a case study approach. The findings show that (1) IPS learning in the seventh grade at SMPN 1 Ngunut is effective in instilling discipline and responsibility, (2) Teachers use teaching activities to instill values such as punctuality and task completion, (3) Through methods like group work, individual assignments, and behavioral evaluations, students show positive changes, (4) The role of teachers as facilitators and role models is crucial, (5) Collaboration between teachers and the principal creates a school culture that supports character development, and (6) The impact of this process is reflected in increased student awareness of their responsibilities. These findings highlight that IPS not only fosters cognitive knowledge but also serves as a strategic medium for continuous moral and character development.